2018
DOI: 10.5194/wes-3-573-2018
|View full text |Cite
|
Sign up to set email alerts
|

Applications of satellite winds for the offshore wind farm site Anholt

Abstract: Abstract. Rapid growth in the offshore wind energy sector means more offshore wind farms are placed closer to each other and in the lee of large land masses. Synthetic aperture radar (SAR) offers maps of the wind speed offshore with high resolution over large areas. These can be used to detect horizontal wind speed gradients close to shore and wind farm wake effects. SAR observations have become much more available with the free and open-access data from European satellite missions through Copernicus. Examples… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…In recent years, however, a number of analytical and experimental studies, as well as numerical investigations, have revealed that offshore wakes may extend to several dozens of kilometers downstream, in particular when the wind farm is large and when the atmospheric stratification is stable. Particularly in coastal environments, such as the North Sea, airflow from the land on warm days brings warmer air over the cooler sea surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, however, a number of analytical and experimental studies, as well as numerical investigations, have revealed that offshore wakes may extend to several dozens of kilometers downstream, in particular when the wind farm is large and when the atmospheric stratification is stable. Particularly in coastal environments, such as the North Sea, airflow from the land on warm days brings warmer air over the cooler sea surface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, meteorological masts, dual‐Doppler radar, and scanning‐Doppler lidar provide high‐resolution data but are limited by their fixed locations, restricting the measurement of wakes to certain wind directions and/or limited distances from the wind farm. Satellite‐based synthetic aperture radar (SAR) observations enable the measurement of wakes over larger areas, but the spatial resolution of the raw images limits the level of detail that can be observed. In contrast, direct aircraft observations combine the advantages of in situ measurements directly within the wake with a large spatial coverage, but at the cost of a relatively long sampling time.…”
Section: Introductionmentioning
confidence: 99%
“…Methods to deal with few satellite samples include the hybrid method (Badger et al, 2010) and the gap-filling method during periods with a lack of data due to sea ice (Doubrawa et al, 2015). The adjustment for few samples and for uneven diurnal or seasonal sampling only makes sense to perform for local sites or regions (Ahsbahs et al, 2019) rather than for all the European seas. In the case meteorological observations are accessible, these can be useful for comparison and adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Satellite winds retrieved at 10 m height are averaged into wind resource statistics using the software for SAR-based wind resource assessment (Hasager et al, 2008(Hasager et al, , 2011Ahsbahs et al, 2019) and for ASCAT using the methodology presented in Karagali et al (2018b). Wind turbines offshore have hub heights at around 100 m height.…”
Section: Ascat and Sar Ocean Wind Processingmentioning
confidence: 99%
“…The spatial resolution is around 1 km or less, and although it is a better resolution than what can be obtained using microwave scatterometers, it is still relatively coarse. A summary of the use of synthetic aperture radars for wind measurements can be found in Dagestad et al (2013) and a recent application at the Anholt wind farm is discussed by Ahsbahs et al (2018).…”
Section: Satellite-based Measurementsmentioning
confidence: 99%